The Acute Single and Mixture Toxicity of Paraquat Dichloride and Deltamethrin to Guppy (Poecilia reticulata) - Rully Adi Nugroho; Cornelis Adrianus Maria van Gestel (HAYATI Journal of Biosciences, 2022)
Although herbicide and insecticide contamination of surface waters normally occurs in the form of mixtures, the toxicity interactions displayed by such mixtures have only rarely been characterized. This study evaluated the acute effects of single pesticides (paraquat dichloride and deltamethrin, tested in their commercial formulations Gramoxone 276 SL and Decis 25EC) and their equitoxic mixtures on the survival of adult male guppy fish (Poecilia reticulata). Mixture toxicity was evaluated against the reference models of Concentration Addition (CA) and Independent Action (IA). In the single treatments, the 72h LC10 and LC50 values were 1.5 and 6.0 mg a.s. L-1 and 0.53 and 3.6 µg a.s. L-1 for paraquat dichloride and deltamethrin, respectively. The equitoxic mixtures showed significant paraquat dichloride-deltamethrin antagonism, both based on the CA and the IA model, without significant dose-level dependent deviations.